Hal-Hal yang Mengganggu, Menggoda, atau Tantangan Bagi Manusia dalam Manajemen Pendidikan Islam (Telaah Ayat-Ayat Al-Qur’an, Hadis) - Elvarisna, Elvarisna; Sari, Rahmi; Bustamam, Risman (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This article aims to identify and analyze the factors that disturb, tempt, or become obstacles in the implementation of Islamic education management, by referring to verses of the Qur'an and the hadith of the Prophet Muhammad SAW. This research employs a qualitative approach using literature review methods, where data is collected from tafsir books, hadiths, books on Islamic education management, and relevant scholarly journals. The data analysis technique is conducted in a descriptive-qualitative manner with a thematic approach, which involves grouping and interpreting religious texts based on the theme of worldly temptations in the context of leadership and educational management. The results of the study indicate that wealth and position have the potential to obscure the trust of leadership, family can become a trial that hinders justice, while worldly games and the temptations of Satan can lead to neglect and conflict in the management of educational institutions. Therefore, Islamic educational management needs to be built upon spiritual values and Islamic leadership ethics that emphasize trust, justice, and responsibility. This study recommends strengthening faith, internalizing Qur'anic values, and developing a spiritually-based management system to tackle these challenges professionally and with integrity.